Recent evolution and characteristics of the foreign population in Madrid - Lora Tamayo D’ocón, Gloria (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This paper analyzes the role of Madrid concerning foreign immigration in Spain, based on the latest statistical data. It draws the evolution, characteristics and spatial distribution of foreigners in the Community and the city of Madrid. It also points out some of the consequences of the rapid growth of immigration in the territory.